Peningkatan Aktivitas Belajar Peserta Didik pada Pembelajaran Ekonomi Melalui Game-based Learning Model Menggunakan Media Wordwall - Rani Faniamawati; Buchori Agus Wahyudi; Dhiah Fitrayati (Unika Santu Paulus Ruteng, 2023)
The 21st century education is student-centered education and can not independent of technological development. Based on observations in the class of X-7 SMA Negeri 1 Driyorejo, learning activities at low levels, this learning activity appears to be based on learning activities using a group discussion method. Viewing such low learning activities, researchers are intended to implement a game-based learning model as an effort to improve student learning activities. Thus, this research was conducted with the aim of increasing students learning activities in economics learning through game-based learning model using wordwall media. This study consists of two cycles of four stages each of which is planning, implementation, observation, and reflection. The instruments used in this study are observation sheets of student learning activities with 7 aspects as indicators of learning activities used. The 7 aspects are 1) participating in assignments; 2) involved in problem solving; 3) ask a teacher or friends if they do not understand the issue; 4) trying to find the information needed for problem solving; 5) carry out group discussions as the teacher instructs; 6) assessing abilities and results; 7) use and apply what is found in completing a task. The research result that game-based learning models using wordwall media can increase student learning activities in economic learning.